THE EFFECT OF NON PERFORMING FINANCING AND NET INCOME ON FINANCING AT BSI 2023 TO 2025 - Ami Nullah Marlis Tanjung; M. Guffar Harahap (CV. Barokah Publsiher, 2025)
The rapid growth of Islamic banking today, accompanied by an increase in the number of Islamic banking customers, is an interesting phenomenon in the midst of a dual banking system. This study aims to determine and analyse the effect of Non Performing Financing (NPF) and Net Income (NI) on Financing at KB Islamic Banks from 2023 in the first quarter to 2025 in the fourth quarter. The data used is the financial report of KB Bank Syariah which has been published on the website www. Bank Syariah Indonesia.co.id. The method of analysis in this study is an associative method, with classical testing, and statistical analysis, namely multiple linear regression analysis. The variables of this study are Non Performing Financing (NPF) as variable X 1 and Net Income (NI) as variable X 2 and Financing as Y. The results of the analysis using the statistical t test with a significant (α) = 0.05 using the sig value from the SPSS output obtained the significance value of each independent variable Non Performing Financing (NPF) (0.00) and Net Income (NI) (0.655). The Total Asset variable alone has a partial influence on financing, while the Net Interest variable is far above the significance of 0.05 and this identifies that there is no partial influence on financing. The results of the analysis with the F test with a significance (α) = 0.05 obtained a significance of 0.000. This value is not greater than the significance value of 0.05 and this indicates that there is a significant relationship between Non Performing Financing (NPF) and Net Income (NI) on financing simultaneously.